Factors associated with maternal mortality among women of reproductive age seeking care at Wajir County Referral Hospital, Wajir County, Kenya - Fatuma, Jimale Alim; Mbugua, Samuel; Marwa, Immaculate Nyaseba (International Journal Of Community Medicine And Public Health, 2025)
Background: The rate of maternal death is too high. In 2020, 287,000 women lost their lives both during and after becoming pregnant and giving birth. In 2020, low- and lower-middle-income countries accounted for nearly 95% of all maternal deaths, the majority of which could have been avoided. The study aimed to determine factors associated with maternal mortality among women of reproductive age seeking care in Wajir County, Kenya. Methods: The study employed a retrospective analytical cross-sectional study design where a systematic random sampling approach was utilized to recruit respondents into the study. The Yamane formula of sample size calculation was used to recruit 359 study partakers for this study. Results: The prevalence of maternal mortality in Wajir County was 4.2%. Not utilizing emergency obstetric and newborn care services (OR=2.4,95%CI=0.19-0.89), unavailability of skilled birth attendants (OR=2.4,95%CI=0.19-0.87), poor uptake of antenatal care services (OR=3.1,95%CI=0.15-0.67), and study partakers aged 18-23 years (OR=3.7,95%CI=0.06-3.89), earning 1-10000 Ksh (OR=5.3,95%CI=0.04-0.89) increased the odds of maternal mortality rate. While taking 31-60 minutes to reach the nearest health facility (OR=3.9,95%CI=1.67-9.23) and being married (OR=3.9,95%CI=1.47-10.54) reduced the odds of maternal mortality. Conclusions: The prevalence of maternal mortality in Wajir County was 4.2%. From this study, not utilizing emergency obstetric and newborn care services, unavailability of skilled birth attendants, and study partakers aged 18-23 years increased the odds of maternal mortality rate. While taking 31-60 minutes to reach the nearest health facility and being married reduced the odds of maternal mortality.